Aktualisasi dalam upaya meningkatkan kepercayaan dan stabilitas risiko bank syariah - Fadhilah, Moh Nur (Maliki Interdisciplinary Journal, 2025)
Islamic banking in Indonesia has experienced rapid development, but still faces significant challenges in maintaining public trust and risk stability. The main problems faced are low Islamic financial literacy, lack of understanding of Islamic principles, and weak implementation of risk management in accordance with Islamic values. In addition, service accessibility, digitalization quality, and operational transparency also affect customer perceptions and loyalty. Global economic uncertainty, regulatory pressure, and potential financing risks reinforce the urgency of the need for relevant and adaptive strategy actualization. This study aims to examine how actualization in various aspects - such as improving services, digital innovation, implementing Islamic social values, and integrated risk management - can increase trust and maintain the financial stability of Islamic banks. Using a literature review approach, this study concludes that actualization must be part of a sustainable and value-based long-term strategy. This approach not only strengthens the position of Islamic banks in the national financial system but also builds institutional resilience in facing economic and social challenges. Thus, trust and stability can be achieved through synergy between values, strategies, and consistent implementation.